Meningkatkan Kualitas Official Statistics Melalui Integrasi Big Data - Nisa Hayatun Nufus (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
This paper delves into the transformative impact of incorporating big data into official statistical practices. The objective is to elevate the overall quality of data by leveraging the potential of big data analytics. The study employs a comprehensive methodology that encompasses data collection, processing, and analysis. The primary aim is to explore how the integration of big data can enhance the accuracy, timeliness, and relevance of official statistics. The research methodology involves the systematic collection of large-scale datasets, followed by advanced analytics techniques to extract meaningful insights. The findings underscore the substantial improvements achieved in the precision and reliability of official statistics through the infusion of big data methodologies. The transformative potential of integrating big data into official statistics is explored, offering valuable insights for policymakers, researchers, and practitioners in the field.